High Resolution through Graded-Index Microoptics. (11th July 2012) - Kotlyar, Victor V.; Kovalev, Alexey A.; Nalimov, Anton G.; Stafeev, Sergey S.
Abstract : By solving Helmholtz equations, relationships to describe propagating modes in an arbitrary graded-index planar waveguide are derived. We show that in the quadratic- and secant-index waveguides a minimal mode width is 0.4λ / n, whereλ is the wavelength in free space andn is the refractive index on the fiber axis. By modeling in FullWAVE, we show that the high-resolution imaging can be achieved with half-pitch graded-index Mikaelian microlenses (ML) and Maxwell's "fisheye" lenses. It is shown that using a 2D ML, the point source can be imaged near the lens surface as a light spot with the full width at half maximum (FWHM) of 0.12 λ . This value is close to the diffraction limit for silicon (n = 3.47 ) in 2D mediaFWHM = 0.44 λ / n = 0.127 λ . We also show that half-pitch ML is able to resolve at half-maximum two close point sources separated by a 0.3 λ distance.